The Role of Macrocyclic Compounds as Supramolecular Drug Delivery Systems: A-Review - Saputra, Muhammad Furqon Novryan; Nursofia, Yesi; Tarigan, Indra Lasmana (Chempublish Journal, 2025)
In recent decades, significant advances in the development of drug delivery systems have unlocked new possibilities for enhancing therapeutic efficacy. Among the diverse range of innovative materials, macrocyclic-based supramolecular systems have emerged as promising platforms due to their unique physicochemical properties. Macrocyclic compounds such as cyclodextrins and cucurbiturils exhibit a remarkable ability to form stable inclusion complexes with various drug molecules, thereby improving their solubility, chemical stability, bioavailability, and pharmacokinetic profiles. This review highlights the design principles, synthetic strategies, and mechanisms of action underlying macrocyclic drug carriers, with particular emphasis on their responsiveness to environmental stimuli such as pH, temperature, and biomolecular triggers. Recent findings demonstrate that macrocyclic systems can significantly enhance drug loading efficiency, targeted delivery, and cellular uptake, while minimizing systemic toxicity. These advances underscore the potential of macrocyclic supramolecules as foundational elements for the development of next-generation drug delivery systems that are more precise, effective, and adaptable to personalized therapeutic needs.